Platelet/Lymphocyte ratio independently predicts the outcome of severe aplastic anemia patients treated with antithymocyte globulin - Dong,Peiyuan (2021)
SUMMARY OBJECTIVE: The aim of this study was to determine the clinical role of platelet/lymphocyte ratio and neutrophil/lymphocyte ratio in severe aplastic anemia patients treated with antithymocyte globulin. METHODS: The outcomes of consecutive severe aplastic anemia patients treated with rabbit or swine antithymocyte globulin plus cyclosporine (n=159, from January 2012 to December 2018) were analyzed retrospectively. RESULTS: In a total of 159 patients, the actuarial 5-year survival rate was 85.6%. Low platelet/lymphocyte ratio (PLR≤55) was significantly associated with less complications at 1 month and 24 months after the antithymocyte globulin treatment (p=0.048 and 0.028, respectively). The univariate and multivariate analyses revealed that low platelet/lymphocyte ratio was an independent predictor of overall survival (p=0.03 and 0.04, respectively). Patients with low neutrophil/lymphocyte ratio (NLR≤0.18) had shorter survival time, but there was no significant difference (p=0.056). PLR was positively correlated with neutrophil/lymphocyte ratio (r=0.38, p<0.0001) and age (r=0.17, p=0.0379), while it was negatively correlated with IgG level (r=-0.18, p=0.0309). The ratio of CD4/CD8 was significantly higher in low platelet/lymphocyte ratio group (p=0.005). CONCLUSION: The platelet/lymphocyte ratio reflects the immune abnormality of SAA. Notably, low platelet/lymphocyte ratio is an independently positive prognostic factor for severe aplastic anemia patients treated with antithymocyte globulin.